Mistaking Conscience for Control: Why Institutional Conscience Claims are an Unethical Gambit. - Moore, Bryanna; Shaw, Marjorie Hodges (American Journal of Bioethics, 2026)
The article critically examines Wasserman et al.'s defense of institutional conscience rights for secular hospitals, which argues that secular healthcare organizations can claim conscience protections to refuse interventions they find objectionable, particularly in cases involving patients who are neurologically devastated. While acknowledging the authors’ claim that institutions can possess moral commitments akin to conscience, the article raises concerns about the practical and ethical implications of allowing institutions to override patient and family preferences through conscience-based objections. It highlights potential risks such as undermining shared decision-making, privileging clinicians’ values over those of patients and families, and disregarding the diversity of moral perspectives within healthcare teams. The article calls for a more nuanced consideration of institutional moral identity, the complexities of disorders of consciousness, and the importance of patient- and family-centered care in resolving intractable treatment disagreements.